Factors influencing transitional care from adolescents to young adults with cancer in Taiwan: A population-based study. Issue 1 (December 2016) - Jin, Yo-Ting; Chen, Chin-Mi; Chien, Wu-Chien
Abstract Background To investigate the progress of transition from paediatric to adult health care for patients with cancer in Taiwan's medical system. Methods The data were retrieved from the Longitudinal Health Insurance Database (LHID), which contains the original inpatient and outpatient medical claims data for 1, 000, 000 enrollees randomly sampled from the NHIRD between 1997 and 2010. Results Among the 1, 411 cancer patients selected for this study, 98.09 % received adult-oriented therapy before the age of 18. In addition, only 1.91 % of the patients received paediatric-oriented therapy during adolescence. The primary factors that determine whether these patients would receive paediatric-oriented therapy or adult-oriented therapy at an early age were as follows: the age of the patient at the first visit and the performance-level of the hospital (p < 0.001). Conclusions Previous studies conducted in developed countries have demonstrated that the unwillingness of patients to switch from paediatric-oriented therapy to adult-oriented therapy being the major obstacle that hinders the transition process. However, this study revealed a different result: the implementation of the National Health Insurance system in Taiwan makes healthcare affordable for the adolescent patients who may not possess adequate knowledge about paediatric health care and may not appreciate paediatric-oriented therapy, thereby hindering the transition process.